2021
DOI: 10.24875/gmm.20000665
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and COVID-19

Abstract: La pandemia de enfermedad por coronavirus 2019 ha afectado a todas las dimensiones de la atención en salud, entre ellas el aseguramiento de la lactancia materna exclusiva y su promoción. El riesgo de contagio y las consecuencias de la pandemia han provocado preocupación entre las futuras madres o las que se ya encuentran lactando debido al riesgo de una posible transmisión del virus a través de la leche materna. Aunque aún no se ha detectado el coronavirus 2 del síndrome respiratorio agudo grave (SARS-CoV-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Although there is no evidence to suggest that COVID-19 can be transmitted through breast milk, breastfeeding women diagnosed with the virus reported that their main concern was transmitting it to their newborn [ 9 ]. It can be transmitted via aerosol during the breastfeeding process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no evidence to suggest that COVID-19 can be transmitted through breast milk, breastfeeding women diagnosed with the virus reported that their main concern was transmitting it to their newborn [ 9 ]. It can be transmitted via aerosol during the breastfeeding process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, children were separated from mothers in several hospitals. Such behaviour was not in line with WHO recommendations (Rao et al, 2021) and, 2 years after the outbreak, it resulted in a further decrease in trust in hospital deliveries (Galindo‐Sevilla et al, 2021; Muñoz‐Amat et al, 2021; Rao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a last option, formula milk can be considered as well. However, it is important to note that human milk should be prioritized [ 48 ].…”
Section: Discussion (Table 1 )mentioning
confidence: 99%